PERFORMANCE OF SPECIFIC GROWTH RATE VANNAMEI SHRIMP USING EM4 PROBIOTICS IN MAINTENANCE MEDIA - Sogho, Sevin F. A. Kae; Jasmanindar, Yudiana; Djonu, Asriati (Journal of Aquaculture Development and Environment, 2023)
Vannamei shrimp cultivation that applies intensive and supra-intensive technology using high stocking density treatment and maximum feeding has negative impacts such as organic waste from leftover feed and feces which causes growth in shrimp to be disrupted. This research aims to determine the effectiveness of adding EM4 probiotics to rearing media on the growth rate of vannamei shrimp. This research used a completely randomized design (CRD) with four treatments, namely without administration of probiotics, with addition of probiotics in maintenance media of 1 ml/l, 3 ml/l and 5 ml/l. The parameters measured in this research were the specific growth rate during the 28 days of rearing period. The results showed that giving probiotics at a dose of 1 ml/l gave the best specific growth rate of 3.47 g%/day on the 28th day.